Effect of Different Ionic Surfactants on the Structural, Photophysical, and Morphological Properties of Water‐Based P3HT:PCBM Nanoparticle Dispersions and Films. (15th December 2020) - Bellacanzone, Christian; Prosa, Mario; Muccini, Michele; Ruani, Giampiero; Seri, Mirko; Bolognesi, Margherita
Abstract: Aqueous suspensions of composite nanoparticles of poly(3‐hexylthiophene) (P3HT) and [6, 6]‐phenyl C61 butyric acid methyl ester (PCBM) are fabricated by miniemulsion method using three different ionic surfactants. The aim is to study how the length and conformation of the surfactants alkyl chains affect the properties of the nanoparticles. While the morphology and dimensions of the nanoparticles are similar, UV–vis spectroscopy evidences that the internal aggregation and ordering of the P3HT chains varies within the three nanoparticle formulations. The surfactant with branched alkyl chains promote the highest degree of ordering of P3HT chains in the nanoparticles (leading to increased conjugation length). In contrast, the lowest ordering is found for the nanoparticles with the surfactant having the shortest linear alkyl chain. The optical/structural properties of nanoparticles are partially retained in the films. Besides, the surfactant with branched alkyl chains favors the strongest coalescence of nanoparticles in the thin film, promoting a further ordering of the polymeric chains in the most external shell of the nanoparticles as evidenced by steady‐state and time‐resolved UV–vis spectroscopy and confocal fluorescence microscopy. These findings might guide the engineering of new surfactants for composite nanoparticles for optoelectronic applications. Abstract : A study of the effect of ionic surfactants on the properties of P3HT:PCBM composite nanoparticles is presented. The branched alkyl chains of dioctylsulfosuccinate sodium salt promote higher crystallinity of P3HT in the nanoparticles and favor their coalescence when deposited into films. The conjugation length increases and the film is more compact and homogenous, which are fundamental requirements for optoelectronic devices functioning.